Serum Adiponectin status as a Biomarker of metabolic syndrome among Malaysians - Md Aris, Mohd Aznan; Draman, Samsul; Abdullah, Nor Zamzila; Mohd Rus, Razman; Khattak, Muhammad Muzaffar Ali Khan (2011)
Adiponectin is a collagen-like circulating protein secreted by adipocytes. Several studies have demonstrated that low adiponectin also has strong association with metabolic syndrome components such as it is decreased in obesity, insulin resistance, type 2 diabetes, dyslipidemia and coronary artery disease. The objective of this study was to determine and compare the level of adiponectin between metabolic syndrome and non-metabolic syndrome subjects. A cross-sectional comparative study was carried out among 76 participants of metabolic syndrome and 76 participants of non metabolic syndrome based on IDF criteria. This study was held at three primary care clinics and two villages in Kuantan, Pahang from 1st March to 30th September 2009. The majority of respondents were Malay (88.8%) and female (57.9%) adult with mean age of 51 years old. Most of them are non-smoker (77.6%) and had history of Hypertension (51%) and Diabetes Mellitus (46.4%) with mean waist circumference of 88.5 cm and mean weight of 66.6kg. The study revealed that age, weight, waist circumference, blood pressure, fasting glucose, HDL-Cholesterol and triglycerides were significantly different in both group (P<0.05). The metabolic syndrome group had a significantly lower adiponectin concentration than non-metabolic syndrome group (mean: 11.64 ug/ml vs 13.21 ug/ml; P<0.05). Hence, this study concluded that serum adiponectin was a significant biomarker for metabolic syndrome.